Mathematics competition in Šiauliai college - Rimkevičienė, Audronė; Kačinskaitė, Roma; Garbaliauskienė, Virginija; Šedžiuvienė, Natalija (Lietuvos matematikos rinkinys, 2010)
In this article, we survey the mathematics contest, which is held for first-year students of Šiauliai College. We discuss on the organize grounding of competition and its perspective, and on the benefit of students motivated for learning. Also, we analyze an example of the tasks and the most common errors made by students.
Keywords: mathematics competition; skills assessment; assignments; mistakes